Convergence of Multiple Fourier Series of Functions of Bounded Generalized Variation - Goginava, U.; Sahakian, A. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
The paper introduces a new concept of Λ-variation of multivariable functions and studies its relationship with the convergence of multidimensional Fourier series.